Efficacy of Glyceryl Trinitrate Ointment for Perianal- Intrarectal Local Anesthesia in Transrectal Ultrasound- Guided Prostate Biopsy- Compared to Topical Lignocaine - Islam, SK Amirul; Alam, AKM Khurshidul; Rahman, Mohammad Shafiqur; Islam, Md Monowarul; Rahman, Mohammed Mizanur; Saha, Pranashis (Bangladesh Journal of Urology, 2020)
Objective: Anorectal pain and discomfort during transrectal ultrasound (TRUS)-guided prostate biopsy is an important issue of this procedure. Therefore present study was designed to compare whether the use of topical glyceryl trinitrate (GTN) ointment or lignocaine gel is more effective as an adjunct to periprostatic nerve block (PPNB) in reducing pain associated with transrectal ultrasound (TRUS)-guided prostate biopsy. Methods: In all, 120 consecutive patients having their first TRUS-guided prostate biopsy were randomized to receive either 0.4% GTN ointment or 2% lignocaine gel, 10 minutes or 5 minutes respectively before biopsy. All patients had a biopsy preceded by an injection with 5 ml of 2% lignocaine local anaesthesia. Results: A 100-point visual analogue score was used to record overall pain due to the presence of the probe, the biopsy itself and pain after the procedure. There was no significant difference in age, PSA level and prostate volume between the groups. There was a significantly lower mean pain score due to probe insertion, in the GTN than lignocaine group (18.32 vs 37.48, P < 0.001); pain perception was lower for the whole procedure in the GTN group (16.59 vs 35.17, P < 0.001); and was most pronounced in men aged d”65 years (21.45 vs 40.7, P < 0.001). Five patients (8.3%) in the GTN group complained of headache. Conclusion: So it can be concluded that, topical GTN ointment is safe and effective in reducing the discomfort and pain associated with TRUS-guided prostate biopsy, in particular the insertion of the ultrasound probe. It might be of maximum benefit in the younger patient(d”65years). Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.14-19